The art of Translation: Essential Translation Techniques, Principles and Strategies with the use of professional tools on diverse documents and texts from English to Spanish - Paredes Baiza, Roberto Arturo; Magaña González, Marta Edith; Deras Andrade, Reyna Elizabeth (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte digital